Partisipasi Masyarakat Dalam Penanggulangan Kemiskinan ( Studi Kasus Pada PNPM-MP Di BKM â Tri Daya Waru Mandiriâ Kelurahaan Karangwaru Kota Yogyakarta ) - , HERAWATI, DRA, Dr. Agus Pramusinto, MDA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was animed two know societyâs participation in the poverty tackling through PNPM-MP. As the aim researcher wants to focus on seeing how the societyâs participation inplemented in participative building program. Therefore, the researcher limits obyects on Badan Keswadayaan Masyarakat (BKM) and Unit Pengelola Kegitan and also Kelompok Swadaya Masyarakat (KSM) by explaining the level difference of societyâs participation in KSM. The researcher was obyect Badan Keswadayaan Masyarakat BKM âTridaya Waru Mandiriâ in Kelurahan Karangwaru, Yogyakarta. That has been rceived Bantuan Langsung Masyarakat (BLM). This research was using qualitative method through indepth interview with some informants, and analysis technique utilized was secondary data processing. From the research results, it showed that the implementation of PNMP Mandiri done by BKM âTri Daya Waru Mandiriâ through UPL, UPS, and UPK activity could run well as its purposes, however there were still many obstacles which were less know society are lazy and had ni spirit of effort and the low most society awarness about responsibility to implement duty, so it caused some program receivers were not able to develop KSM maximally. The other impication was the raise of conflic to make the group for not developing together. The research results indicated that there was difference of society participation level both KSM, Eventhough at the beginning both of them had relative some condition and quality. KSM Anggrek was independent KSM and KSM mMakmur Jaya was growing KSM. The difference of achievement level indicated the defferent participation level experienced by KSM in the development, caused by some factors. Therefore, the author recommended that the government as the party who conveyed PNMP-MP progran was not only to build administrative, but also program implementation relationship withtthe society. BKM as the program implementer should give more attantion to reciver selection process in the future ecspecially criteria factor of the candidates of program reciever to run well and meet the target. Besides, it should made a mechanism to ask responsibolity of program advantage reciver group, including to determine punishment if there was program that did not run well. It is aimed to prevent program for misuse in the society, improve program success asurance in reforming the society live quality and incrase performance achievement of a program.